PROFESSIONAL DEVELOPMENT EFFECT ON LIBRARIAN PERFORMANCE - Kusumawardhani, Dwininda; Djunaedi, Achmad (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Bckground of the study: Professional development is an activity to increase and improve knowledges, attitudes, and skills that are useful for librarians in carrying out their duties in the library. Padjadjaran University librarians have participated in professional development activities such as attending seminars, workshops, conferences, etc. Librarians? competencies are obtained from professional development activities which are the most important elements for librarians? performance improvement. This study discusses how the influence of needs, resources, administrative support, and librarians? professional development impacted on the performance of librarians at Padjadjaran University Library (UNPAD).Purpose: The purpose is to determine the extent of the influence of needs, resources, administrative supports, and the developments of the librarians? profession on their performance.Method: This study uses a quantitative approach, with independent variables of professional development (Pan and Hovde, 2010) consisting of needs for professional development, resources for professional development, and administrative support; while the dependent variable is the librarians? performance (Bernardin and Russell, 1993). The samples were collected using the total sampling method for 87 people in total. The data were tested using validity test, reliability test, multiple regression tests, and hypothesis testing with t-test and f-test.Findings:The results of this study indicate that simultaneously there is a significant influence of professional development on the performance of librarians. And partially, the needs for professional development has a significant influence on performance, resource for professional development has a significant influence on performance, while the Administrative Support does not have any significant influence on library performance. Conclusion: The conclusion of this study is that librarians have participated in professional development activities, both internally and externally. Although they do not get support from a complete institution.